2009
DOI: 10.1186/1476-7120-7-30
|View full text |Cite
|
Sign up to set email alerts
|

Ozone and cardiovascular injury

Abstract: Air pollution is increasingly recognized as an important and modifiable determinant of cardiovascular diseases in urban communities. The potential detrimental effects are both acute and chronic having a strong impact on morbidity and mortality. The acute exposure to pollutants has been linked to adverse cardiovascular events such as myocardial infarction, heart failure and life-threatening arrhythmias. The long-terms effects are related to the lifetime risk of death from cardiac causes. The WHO estimates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 37 publications
1
43
0
1
Order By: Relevance
“…Results of our study revealed a negative correlation between O 3 concentrations and CVD-related emergency visits, which is in line with previous studies (22)(23)(24). However, many studies showed destructive effects of this pollutant on the cardiovascular system.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Results of our study revealed a negative correlation between O 3 concentrations and CVD-related emergency visits, which is in line with previous studies (22)(23)(24). However, many studies showed destructive effects of this pollutant on the cardiovascular system.…”
Section: Discussionsupporting
confidence: 82%
“…Several review studies (2,9,22) showed that O 3 was one of the most toxic compounds of mixed photochemical smog. Results of our study revealed a negative correlation between O 3 concentrations and CVD-related emergency visits, which is in line with previous studies (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Increased risk of paroxysmal atrial fibrillation episodes (Rich et al, 2005), ventricular arrhythmias (Rich et al, 2006), reduction of heart rate variability, and increased resting heart rate have been reported (Zanobetti et al, 2010). A recent review of Srebot and colleagues (Srebot et al, 2009) extensively examined the available knowledge on the pathways connecting ozone and cardiovascular adverse effects, including influence on macrovascular diameter and tone, increased peripheral blood pressure, short-term autonomic imbalance, effects on inflammation response, and increased oxidative stress in the cardiovascular system.…”
Section: Discussionmentioning
confidence: 96%
“…Less is known, however, about mechanisms mediating O 3 -induced cardiovascular responses (U.S. EPA, 2013b). Preliminary evidence implicates altered autonomic tone, systemic inflammation, vascular oxidative stress, and endothelial/vascular dysfunction (Srebot et al, 2009).…”
Section: Case Report 2: Particulate Matter Ozone and Cardiovascularmentioning
confidence: 99%